FACTORS INFLUENCING THE EFFECTIVENESS OF THE TRAINING AND VISIT EXTENSION SYSTEM IN LAGOS STATE, NIGERIA - FARINDE , A. J.; JIBOWO, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Crucial factors which influenced the effectiveness of the Training and Visit (T & V) extension system in Lagos State were isolated through factor analytical technique. Data were collected from 214 full-time farmers and 73 village extension agents (VEAs) of the Lagos State Agricultural Development Project (LSADP) in 1994. Eight groups of factors were isolated from farmer-related variables with 25.62% contributions to change in effectiveness of the T & V extension system. Eighteen groups of factors were also isolated from extension worker and organization related variables with 97.15% contributions to effectiveness. However, factors related to the personality development of the extension personnel were found more influential to the effectiveness of the T and V extension system than factors related to the functional imperatives and both internal and field operations of the T and V extension system.